ANALISIS PEMIDANAAN PADA PUTUSAN PENGADILAN NEGERI DEPOK NOMOR 392/PID.B/2018/PN DITINJAU DARI PERLINDUNGAN KORBAN YANG MENYANDANG DISABILITAS - Heski Manura Felinda; Rugun Romaida Hutabarat (Fakultas Hukum Universitas Tarumanagara, 2021)
People that have disabilities should have the same position,rights and also obligations as a normal people in general. Based on Law Nmber 39 of 19.99 about Human Rigmhts. Law Number 8 of Year 2.016 about Peoplewith Disabilities is a form of legal protection, and the fulfillment of rights that should be given to people with disabilities. But in fact, many people that have disabilities still have not received legal protection fully. Even when people with disabilities become victims of crimes, they experience difficulties in court proceedings due to their condition, which can be said when dealing with the law, people with disabilities are discriminated against, law enforcers and legal arrangements still assume that they are some groups of people who are not normal are neither capable nor legally competent in the judicial process. This research form is a normative legal research which is supported by a law approach and a case approach. The research aims to realize legal protection, as well as the fulfillment of the rights of persons with disabilities in court processes. Based on the results of this study, the fulfillent of the rights of people with disabilities as victims and witnesses has not yet been implemented properly in the form of fulfilling the rights of peoples with disabilitie in the face of judicial process, which should receive special treatment and legal equality, based on existing laws and regulations regarding disability people.